Consumable Medical Materials Related To The Treatment Of Covid And Multivitamins During The Pandemic - Vanika, Niken; Yuliawati, Yuliawati; Sani, Fathnur (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
Background: Preparation for self-isolation needs to be prepared with the aim of minimizing the spread of COVID-19 infection, which includes masks, hand sanitizer, oxygen, disinfectants, and others. The demand for multivitamins related to self-isolation needs at Pharmacy X based on observations during the research has fluctuated. For this reason, this research was created to find out the picture of fluctuations/ups and downs in sales of multivitamins and the need for self-isolation for COVID-19 at Pharmacy X, based on observations from January-October 2021. Methods: The method used is the observation method through invoice data for the procurement of multivitamin supplies and self-isolation requirements for each of the 5 multivitamin samples and 5 samples for self-isolation requirements whose demand level is the highest compared to the others. Results: The results obtained from the observation data were fluctuations in sales of multivitamins and the need for COVID-19 self-isolation at Pharmacy X. Conclusion: There has been an increase in sales of multivitamins and the need for self-isolation at Pharmacy X in July 2021 due to the peak incidence of positive cases of Covid-19 infection in Jambi Province while in August-October 2021 it experienced a decline. Keywords: Fluctuation;[ Multivitamin; Self- Isolation; Pharmacy; Covid-19